Left ventricular noncompaction concealed as a case of congestive cardiac failure in a toddler: A case report - Shaifalika Thakur; Sunil Kishore; Rakesh Kumar; Rizwan Ahmar (Journal of Pediatric Critical Care)
Left ventricular noncompaction (LVNC) is a rare congenital structural problem of the heart resulting from the persistence of embryonic myocardium. However, the presentation of this entity, usually in the form of cardiac failure poses a diagnostic dilemma to the treating pediatrician. We report a case of congestive cardiac failure in a 2-year-old which was later discovered to be due to this rare entity. Our case highlights the importance of being open to the possibility of LVNC when a child presents in a cardiac emergency, especially due to its close imitator-hypertrophic obstructive cardiomyopathy. With early recognition, we can thus advance further into preventive pediatric cardiology.